Developing an Intervention to Address Physical Activity Barriers for African–American Women in the Deep South (USA). (May 2013) - Pekmezi, Dori; Marcus, Bess; Meneses, Karen; Baskin, Monica L; Ard, Jamy D; Martin, Michelle Y; Adams, Natasia; Robinson, Cody; Demark-Wahnefried, Wendy
Aim : To address high rates of inactivity and related chronic diseases among African–American women.Materials & methods : Eleven focus groups on physical activity barriers for African–American women in the deep south (USA) were conducted (n = 56). Feedback guided an intervention development process. The resulting Home-Based Individually Tailored Physical Activity Print intervention was vetted with the target population in a 1-month, single arm, pre–post test demonstration trial (n = 10).Results : Retention was high (90%). Intent-to-treat analyses indicated increases in motivational readiness for physical activity (70% of sample) and physical activity (7-day Physical Activity Recall) from baseline (mean: 89.5 min/week, standard deviation: 61.17) to 1 month (mean: 155 min/week, standard deviation: 100.86). Small improvements in fitness (6-Min Walk Test), weight and psychosocial process measures were also found.Conclusion : Preliminary findings show promise and call for future randomized controlled trials with larger samples to determine efficacy. Such low-cost, high-reach approaches to promoting physical activity have great potential for addressing health disparities and benefiting public health.